Antimicrobial and Antioxidant Activities of Sesquiterpenes-Rich Essential Oil of Trichilia monadelpha (Thonn) J.J. De Wilde of Root Bark - Odeja, Oluwakayode Olubunmi; Onocha, Patricia A.; Oloyede, Ganiyat Kehinde; Ayoyerokun, Damola; Ibok, Michael Gabriel; Okpala, Ejike Onwudiegwu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Trichilia monadelpha (Thonn) J.J. De Wilde (Meliaceae) is used in traditional medicine for the treatment of ulcers, cough and inflammatory disorders such as arthritis. In this present study, the essential oil of T. monadelpha root bark was obtained by hydrodistillation using an all-glass Clevenger apparatus. The identification and characterisation were done using Gas Chromatography-Mass Spectrometry. We also, aimed to evaluate the antimicrobial activity of the essential oil against ten micro-organisms using the Agar diffusion method and the free radical scavenging capacity was determined using 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) methods. Twenty (20) different compounds made up the hydrodistilled essential oil, which made up 99.0% of the entire oil content.Â Sesquiterpene compounds made up about 73.3% of the essential oil from the root bark of T. monadelpha, which was described as sesquiterpenes-rich. Sesquiterpenes' most abundant constituents include (E)-Longipinene (18%), 10s,11s-Himachala-3-(12),4-diene (15.26%), Aromadendrene (11.12%), Alloaromadendrene oxide-(1) (8.82%), and Î²-Caryophyllene (5.92%). The essential oil inhibited growth against Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Pseudomonas aerugunosa, Candida albicans, Aspergillus niger, Klebsiella Pneumonia and Salmonella typhi at concentrations of 200 mg/mL to 50 mg/mL with an inhibitory zone of 20 â€“ 10 mm while the antioxidant analysis of the essential oil revealed low scavenging activity which reveals that the synthetic antioxidants were more effective with an Ascorbic acid; IC50 value of 1.47 mgmL-1, Butyl hydroxyanisole; 1.88 mgmL-1, Î±-Tocopherol; 4.83 mgmL-1 followed by the essential oil with an IC50 value of 9.95 mgmL-1. T. monadelpha root bark essential oil contains notable chemical compounds that are responsible for its antioxidant and antimicrobial activities.